Therapeutic Drug Monitoring of Tacrolimus Based on Volumetric Absorptive Microsampling Technique (VAMS) in Renal Transplant Pediatric Recipients-LC-MS/MS Method Development, Hematocrit Effect Evaluation, and Clinical Application - Arkadiusz Kocur; Dorota Marszałek; Jacek Rubik; Agnieszka Czajkowska; Tomasz Pawiński (MDPI AG, 2023)
Tacrolimus (TAC) is post-transplant pharmacotherapy's most widely used immunosuppressant. In routine clinical practice, frequent uncomfortable venipuncture is necessary for whole-blood (WB) collection to check trough TAC levels. Volumetric absorptive microsampling (VAMS) is an alternative strategy to WB collection. In this study, we aimed to validate and develop a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for TAC quantification in WB and VAMS samples. After extraction with water and protein precipitation, the samples were directly analyzed using LC-MS/MS. Whole-blood and VAMS capillary-blood samples were collected from 50 patients treated with TAC during the follow-up visits. The cross-correlation between the developed methods was evaluated using Passing-Bablok regression and a Bland-Altman bias plot. The matrix effect (ME) and carry-over were insignificant for both scenarios. There was a high correlation between the processes and no significant clinical deviation. LC-MS/MS methods were successfully developed and validated in the 0.5-60 ng/mL calibration range. This study demonstrated and confirmed the utility of VAMS-based TAC monitoring in the pediatric population. This is the first study to directly develop and validate the VAMS LC-MS/MS method for evaluating the hematocrit effect in the pediatric population. The statistical correlation between immunochemical and VAMS-based methods was satisfactory.